Legis Ratio of Tax Imposition to the Transfer of Land Rights through Instruction - Suarda, I Gede Widhiana; Prakoso, Bhim; Setiawan, Khafid (Budapest International Research and Critics University, 2022)
Inheritance is a legal event that occurs when a person dies. Inheritance is the process of transferring inheritance from the deceased heir to heirs who are related by blood and marriage to the heir. When a person dies, this creates a legal consequence, namely how the management and continuation of rights and obligations as a result of a legal event due to the death of a person is regulated by inheritance law. Assets obtained from inheritance receipts are one form of additional economic capacity that can be received by a person as regulated in Law Number 36 Year 2008. Problem formulation 1) What is the basis for imposing Tax on heirs to the object of inheritance? 2). Does the imposition of taxes on heirs meet the principles of justice? The methodology used is normative juridical, with a statutory approach, a conceptual approach, and. historical approach. Conclusion That the taxation legis ratio using this approach is a fundamental basis on a philosophical basis which justifies the state to collect taxes as enforceable in the sense of having authority with coercive power. Taxes have become the backbone of a very dominant development wheel. Whereas the imposition of tax on the heirs on the object of inheritance does not meet the principles of justice and benefit to the heirs, because the heirs are subject to BPHTB twice. Suggestion The government should review the products of legislation related to the imposition of taxes with legal considerations that meet the legal objectives of the purpose of imposing taxes on the community. Especially the regulation regarding the determination of NPOPTKP for objects obtained from inheritance in order to take into account the economy of the community because the income level of the community is different.